STATUS HUKUM PERJUMPAAN UTANG DIANTARA PERSEROAN INDUK (PARENT COMPANY) DENGAN PERSEROAN ANAK (SUBSIDIARY COMPANY) - Willy Pramana, I Gede; Arya Utama, I Made; Dewi Kasih, Desak Putu (Acta Comitas : Jurnal Hukum Kenotariatan, 2017)
According to Article 1381 of the Civil Code, there are eleven ways found concerning the abolishment of an obligation. One way of abolishing an obligation is through a set off regulated in Article 1425 of the Civil Code. The set-off is made between companies, particularly between parent companies and subsidiary companies which are not regulated in Article 1425. The set-off here only regulates people as subjects regulating it. Therefore, the formulation of the problem in this study includes why there are debts between parent companies and subsidiary companies, what is the validity of a set-off between parent companies and subsidiary companies, and what legal effect that emerges as a result of a set-off between parent companies and subsidiary companies. The type of research used was a normative legal research based on the absence of norms in Article 1425 of the Civil Code against a set-off made by a parent company and a subsidiary company. This study used a source of legal materials consisting of primary, secondary, and tertiary legal materials. The results showed that the occurrence of debts between a parent company a subsidiary company was caused by two things, that is, a debt agreement emerged was genuinely due to the importance of debt and it was motivated by other agreements. Concerning efforts to pay off debts between a parent company and a subsidiary company through a set-off was legitimate because a parent company and a subsidiary company are an independent legal entity and are then separated based on systematic and sociological interpretation about peoples’ phrases in Article 1425 of the Civil Code which include individuals and legal entities. Therefore, the result of the law of set-off between a parent company and a subsidiary company is the disappearance of legal relationship due to the fact that the debts between the two had been settled. Furthermore supervision of the Director General of Taxation is needed for the set-off made by a parent company and a subsidiary company as it relates to the engineering of debts.